Temporal asynchrony, spatial segregation and seasonal abundance of aphids on apple trees - Perdikis, D.; Lykouressis, D.; Mitropoulou, G.; Tsiantis, P. (ENTOMOLOGIA HELLENICA, 2008)
The species composition and seasonal abundance of aphids and their natural enemies were investigated in an apple orchard located in central Peloponnese. For that purpose shoots were collected at weekly intervals. The aphid species Aphis pomi De Geer (Hemiptera: Aphididae), Dysaphis plantaginea (Passerini) (Hemiptera: Aphididae) and Eriosoma lanigerum (Hausmann) (Hemiptera: Eriosomatidae) were recorded. In both years of the study, A. pomi developed higher populations than the other two species. The population of A. pomi was high in June and July. D. plantaginea was present in April and May, with high numbers mainly in May, whilst E. lanigerum was recorded in low numbers from May to July. The number of aphids was not found to differ significantly between samples collected from the northern and southern part of the trees. The species composition of aphid population on each sampled shoot, documented spatial segregation between A. pomi and D. plantaginea. It was proved that the eggs were more commonly laid near the buds of the central part of the twigs. The natural enemies found were predators belonging to the families of Coccinellidae, Chrysopidae, Syrphidae and Anthocoridae. Generally, their numbers were low.